اتجاهات الطلبة نحو التحول الرقمي بمعهد علوم وتقنيات النشاطات البدنية والرياضية - بوقرعة عماد (My University, 2024)
: ملخص تهدف الدراسة الحالية إلى معرفة اتجاهات الطلبة نحو التحول الرقمي بمعهد علوم وتقنيات النشاطات البدنية والرياضية. وعليه تم طرح التساؤل الرئيسي التالي: ما اتجاهات الطلبة نحو التحول الرقمي بمعهد علوم وتقنيات النشاطات البدنية والرياضية؟ ومنه اندرجت تحته جملة من التساؤلات الجزئية : • هل توجد فروق ذات دلالة إحصائية في اتجاهات الطلبة نحو التحول الرقمي بمعهد علوم وتقنيات النشاطات البدنية والرياضية تعزى لمتغير الجنس؟ • هل توجد فروق ذات دلالة إحصائية في اتجاهات الطلبة نحو التحول الرقمي بمعهد علوم وتقنيات النشاطات البدنية والرياضية تعزى لمتغير المستوى الدراسي؟ • ما اتجاهات الطلبة نحو التحول الرقمي بمعهد علوم وتقنيات النشاطات البدنية والرياضية؟ و تم اختيار عينة الدراسة من طلبة معهد علوم وتقنيات النشاطات البدنية والرياضية بجامعة سوق اهراس شملت 50 طالبا تم اختيارهم بطريقة عشوائية وتم اتباع المنهج الوصفي التحليلي، ولجمع البيانات اعتمدنا على استبيان من إعداد الطالب يحتوي على 32 سؤالا، وتمت المعالجة باستعمال الحزمة الإحصائية Spss، واعتمادا على مجموعة من الأساليب الإحصائية وقد أسفرت النتائج إلى ما يلي: • اتجاهات الطلبة نحو التحول الرقمي بمعهد علوم وتقنيات النشاطات البدنية والرياضية إيجابية. • لا توجد فروق ذات دلالة إحصائية في اتجاهات الطلبة نحو التحول الرقمي بمعهد علوم وتقنيات النشاطات البدنية والرياضية تعزى لمتغير الجنس. • توجد فروق ذات دلالة إحصائية في اتجاهات الطلبة نحو التحول الرقمي بمعهد علوم وتقنيات النشاطات البدنية والرياضية تعزى لمتغير المستوى الدراسي. • اتجاهات الطلبة نحو التحول الرقمي بمعهد علوم وتقنيات النشاطات البدنية والرياضية إيجابية. résumé : L'étudeactuelle vise à déterminer les attitudes des étudiantsenvers la transformation numérique à l'Institut des Sciences et Technologies des Activités Physiques et Sportives. En conséquence, la question principale suivante a été posée : Quelle est l'attitude des étudiants envers la transformation numérique à l'Institut des Sciences et Technologies des Activités Physiques et Sportives ? Elle comprenait un certain nombre de questions partielles : • Existe-t-il des différences statistiquement significatives dans les attitudes des étudiants envers la transformation numérique à l'Institut des Sciences et Technologies des Activités Physiques et Sportives en raison de la variable du sexe ? • Existe-t-il des différences statistiquement significatives dans les attitudes des étudiants envers la transformation numérique à l'Institut des Sciences et Technologies des Activités Physiques et Sportives en raison de la variable du niveau académique ? Quelle est l'attitude des étudiants envers la transformation numérique à l'Institut des Sciences et Technologies des Activités Physiques et Sportives ? L'échantillon de l'étude a été sélectionné parmi les étudiants de l'Institut des Sciences et Technologies des Activités Physiques et Sportives de l'Université de Souk Ahras. Il comprenait 50 étudiants sélectionnés au hasard et la méthode d'analyse descriptive a été suivie. Pour collecter les données, nous avons utilisé un questionnaire préparé par l'étudiant contenant 32 questions, et le traitement a été effectué en utilisant le logiciel statistique SPSS. En se basant sur un ensemble de méthodes statistiques, les résultats ont montré les éléments suivants : • L'attitude des étudiants envers la transformation numérique à l'Institut des Sciences et Technologies des Activités Physiques et Sportives est positive. • Il n'y a pas de différences statistiquement significatives dans les attitudes des étudiants envers la transformation numérique à l'Institut des Sciences et Technologies des Activités Physiques et Sportives en raison de la variable du sexe. • Il existe des différences statistiquement significatives dans les attitudes des étudiants envers la transformation numérique à l'Institut des Sciences et Technologies des Activités Physiques et Sportives en raison de la variable du niveau académique. • L'attitude des étudiants envers la transformation numérique à l'Institut des Sciences et Technologies des Activités Physiques et Sportives est positive. abstract : The present study aims to find out the attitudes of students towards digital transformation at the Institute of Science and Technology of Physical Activities and Sports. Accordingly, the following main question was asked: What is the attitude of students towards digital transformation at the Institute of Science and Technology of Physical Activities and Sports? It included a number of partial questions: Are there statistically significant differences in students' attitudes towards digital transformation at the Institute of Science and Technology of Physical Activities and Sports due to the gender variable? • Are there statistically significant differences in students' attitudes towards digital transformation at the Institute of Science and Technology of Physical Activities and Sports due to the variable of academic level? What is the attitude of students towards digital transformation at the Institute of Science and Technology of Physical Activities and Sports? The study sample was selected from students of the Institute of Science and Technology of Physical Activities and Sports at Souk Ahras University. It included 50 randomly selected students and the descriptive analysis method was followed.To collect the data, we relied on a prepared questionnaire.by the student containing 32 questions, and the processing was carried out using the Spss statistical package, and based on a set of statistical methods, the results resulted in the following: • The attitude of students towards digital transformation at the Institute of Science and Technology of Physical Activities and Sports is positive. • There are no statistically significant differences in students' attitudes towards digital transformation at the Institute of Science and Technology of Physical Activities and Sports due to the gender variable. There are statistically significant differences in students' attitudes towards digital transformation at the Institute of Science and Technology of Physical Activities and Sports due to the variable of academic level. • The attitude of students towards digital transformation at the Institute of Science and Technology of Physical Activities and Sports is positive
Keywords: الاتجاهات; التحول الرقمي; الطلبة; منهاج الجيل الثاني; التحديات; المنهاج; الجيل الثاني.; trends; digital transformation; students; tendances; transformation numérique; étudiants.